1984
DOI: 10.1128/jcm.19.2.175-180.1984
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxin production in relation to taxonomic grouping and source of isolation of Aeromonas species

Abstract: A total of 19 of 20 (95%) strains of Aeromonas hydrophila biovar hydrophila and 16 of 17 (94%) strains of Aeromonas sobria isolated from a variety of clinical and environmental sources were found to be enterotoxin positive. Only 2 of 18 (11%) A. hydrophila biovar anaerogenes and 2 of 13 (15%) unidentified Aeromonas strains from a similar variety of sources produced enterotoxin. No association was apparent between the source of isolation, in particular diarrheal stools, and enterotoxigenicity; 41% of the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 21 publications
2
62
1
Order By: Relevance
“…hydrophila enterotoxin was not neutralized by specific antisera to cholera toxin. Champsaur et al (1982) and Turnbull et al (1984) reported similar results for enterotoxins from clinical and environmental isolates of A . sobria and A. hydrophila.…”
Section: Toxicologymentioning
confidence: 62%
See 1 more Smart Citation
“…hydrophila enterotoxin was not neutralized by specific antisera to cholera toxin. Champsaur et al (1982) and Turnbull et al (1984) reported similar results for enterotoxins from clinical and environmental isolates of A . sobria and A. hydrophila.…”
Section: Toxicologymentioning
confidence: 62%
“…Most isolates are cytotoxic to cell cultures, producing responses similar to those noted with Clostridiumperfringens enterotoxin (Hostacka et al 1982;Cumberbatch et al 1979;Jiwa 1983). Additionally, a number of investigators have reported that some isolates of Aeromoms elaborate a heat-labile, cytotonic enterotoxin that has activity similar to that noted with cholera or E. coli heat-labile enterotoxins (Ljungh et al 1981(Ljungh et al , 1982a(Ljungh et al , 1982bLjungh and Wadstrom 1983;Jiwa 1983;Turnbull et al 1984;Campbell et al 1984). Ljungh and coworkers (Ljungh et al 1981(Ljungh et al , 1982a(Ljungh et al , 1982bLjungh and Wadstrom 1983) isolated two hemolysins and a distinct enterotoxin from A .…”
Section: Toxicologymentioning
confidence: 96%
“…Among the virulence factors are enterotoxin, cytotoxin, and hemolysin. The production of cytotoxin and hemolysin is related to A. hydrophila and A. sobria (Turnbull et al 1984), and the production of hemolysin is associated with enterotoxigenicity (Janda et al 1985). In addition to Aeromonasassociated disease in the very young, the old and the immunocompromised often require antimicrobial therapy.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are highly restricted to both A. hydrophila and A. sobria comparing to A . caviae (Turnbull et al 1984;Kirov et al 1986). There is a strong association (91 %) between enterotoxigenicity and gastroenteritis.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong association (91 %) between enterotoxigenicity and gastroenteritis. Enterotoxin producing strains possess three or more of the following properties: they are Voges-Proskauer positive, do not hydrolyse arabinose, are positive for lysine decarboxylase, ferment sorbitol, are able to grow at 42 or 43C, produce large amount of hemolysin Turnbull et al 1984;Kirov et al 1986;Callister and Agger 1987). In contrast, Singh and Sanyal (1992) found that enterotoxin production did not correlate with these properties in addition to citrate utilization either singly or in combination.…”
Section: Introductionmentioning
confidence: 99%